The Routledge companion to libraries, archives, and the digital humanities
1 online resource.
Keywords: "The Routledge Companion to Libraries, Archives, and the Digital Humanities covers a wide range of issues encountered in the world's libraries and archives as they continue to expand their support of, and direct engagement in, DH research and teaching. In addition to topics related to the practice of librarianship, and to libraries and archives as DH-friendly institutions, we address issues of importance to library and archives workers themselves: labour; sustainability; organisation and infrastructure; and focused professional practices that reflect the increasingly important role of librarians and archivists as active research partners. One of the central motifs of this book is that the "two" fields - DH, on the one hand, and the library, archival, and information sciences on the other - are in fact deeply intertwined, productively interdependent, and mutually reinforcing. We place these on an equal footing, considering how they coexist and collaborate in equal partnership. This Companion will be of interest to DH practitioners and theorists, especially those who work in libraries and archives, and those who work with them. Likewise, "non-DH" (or "not-yet- DH") library and archival administrators, reference and public service librarians, cataloguers, and even those who work primarily with the tangible collections, will find here echoes and implications of the most venerable traditions and practices of our shared profession"--